Landslide Vulnerability Assessment (LVAs): A Case Study from Kota Kinabalu, Sabah, Malaysia - Roslee, Rodeano; Jamaludin, Tajul Anuar; Simon, Norbert (Geological Agency, 2017)
DOI: 10.17014/ijog.4.1.49-59The topic on Landslide Vulnerability Assessment (LVAs) in Malaysia is relatively new and received little attention from geoscientists and engineers. This research paper tries to formulate the concept of LVAs by taking into account the science and socio-economic aspects. A new approach in vulnerability concept is also introduced herein. To achieve this goal, a framework was designed for assessing the LVAs. The framework was formulated semiquantitatively through the development of database for the risk elements (human and properties) based on information from secondary data (technical reports), extensive review of literature, and field observations. The vulnerability parameters included in assessing LVAs are 1) physical implication (building structures, internal materials, property damage, infrastructural facilities, and stabilization actions), 2) social status (injury, fatalities, safety, loss of accommodation, and public awareness), and 3) interference on environment (affected period, daily operation, and diversity). Each considered parameter in the vulnerability assessment is allocated with a certain index value ranges from 0 (0 % damage/victims/period), 0.25 (1 - 25% damage/victims/period), 0.50 (26 - 50% damage/victims/period), 0.75 (51 - 75% damage/victims/period), and 1.00 (75 - 100% damage/victims/period). All of these parameters are compiled and analyzed with â€œLandslide Distribution Mapâ€ (LDM) to generate a â€œLandslide Vulnerability Degree map (LVD)â€. The LDM was produced based on field studies and satellite image interpretations in order to locate the landslide locations in the studied area. Finally, three types of physical, human, and environment vulnerabilities were then classified into five classes of vulnerabilities, namely: Class 1 (< 0.20): Very Low Vulnerability; Class 2 (0.21 - 0.40): Low Vulnerability; Class 3 (0.41 - 0.60): Medium Vulnerability; Class 4 (0.61 - 0.80): High Vulnerability); and Class 5 (> 0.81): Very High Vulnerability. Results from this study indicate that a further study is needed to the areas of high to very high vulnerability only. This LVAs approach is suitable as a guideline for preliminary development planning, controlling, and managing the landslide hazard /risk in the studied area and potentially to be extended with different background environments.